Biochemistry - Berg, Jeremy M Tymoczko, John L Stryer, Lubert (W.H. Freeman, 2007)
"Since its first edition in 1975, this extraordinary textbook has helped shape the way biochemistry is taught, offering exceptionally clear writing, innovative graphics, coverage of the latest research techniques and advances, and a signature emphasis on physiological and medical relevance. Those defining features are at the heart of this edition."--Publisher's website.